The problem of the gift: Theological and ontological contexts of modern thought - Bogatov, Mikhail Alexandrovich; Pavlova, Daria Aleksandrovna (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2024)
Introduction. At the very beginning, the problematic field of the article is outlined: we will not talk about the problem of the gift, but about why the gift becomes a problem. To do this, it is necessary to consider several contexts in which this problem arises. We propose to dwell on two of them: theological and ontological. Theoretical analysis. In a theological context, two currents of twentieth-century thought are examined in connection with their influence on the problem of the gift. Firstly, this is political theology, which agreed that in the era of secularization we inherit Christian meanings, and one of them is the phenomenon of a gift. Secondly, this is theoesthetics, which proposes to consider the position of the secularization of our era as a private and, in fact, already closed project. In the ontological context, it is pointed out that the gift becomes a problem where violence and exchange assert themselves as the norm for understanding being. Conclusion. As a result, the article draws conclusions and poses key questions for further research on the problem of the gift.